1969
DOI: 10.1149/1.2412221
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of 6-Substituted Purines Correlation with Structural and Energetic Characteristics

Abstract: The electrochemical reduction of 6‐substituted purines has been examined over the available pH range by direct‐ and alternating‐current polarography, and the effects of substitution evaluated in respect to significant electrochemical characteristics. Where the 1,6 normaland 3,2N=C bonds are available in the pyrimidine moiety, a four‐electron polarographic wave due to hydrogenation of these bonds is observed; purine itself and 6‐methylpurine give two twoelectron waves. The energy‐controlling step involves red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…As the pH approaches the moderately acidic and neutral range the reduction response decreases analogously to an acid dissociation curve (Fig. 2) because the protonation kinetics under these circumstances contribute progressively to the control of the overall rate of the reduction [17,18]. Therefore, it can be concluded that pH 2.2 is the optimum pH for the determination of the investigated compound using DPP at the DME.…”
Section: Dependence Of the Dpp Peak Of Chlorpyrifos On The Solution Amentioning
confidence: 81%
See 1 more Smart Citation
“…As the pH approaches the moderately acidic and neutral range the reduction response decreases analogously to an acid dissociation curve (Fig. 2) because the protonation kinetics under these circumstances contribute progressively to the control of the overall rate of the reduction [17,18]. Therefore, it can be concluded that pH 2.2 is the optimum pH for the determination of the investigated compound using DPP at the DME.…”
Section: Dependence Of the Dpp Peak Of Chlorpyrifos On The Solution Amentioning
confidence: 81%
“…Similar behavior has been reported for quinoline [14], pyrimidine [15], and purine [16] compounds. According to the general mechanism established for such N-heterocyclic compounds [17,18], the --C=N of the heterocyclic system undergoes in acid to neutral media a totally irreversible electrode reaction with a total uptake of 2e…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical behaviour of guanine and other purine derivatives have received a lot of attention with the aim either of developing analytical methods to monitor nucleosides and their metabolic products, or to aid in interpreting the incompletely understood biological reductions and oxidations of these complex molecules [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical reduction of purine (adenine, and other 6-substituted derivatives) on mercury electrodes is well documented in the literature [2,3,7]. In general they are irreversibly reduced in aqueous media either in two successive steps, where each step involves the addition of two electron and two protons to form the hydrogenated species or in a single 4-electron reduction involving the hydrogenation of the two N C double bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation